Factors influencing women farmers’ participation in agricultural cooperatives in Ondo-State, Nigeria - Oluwatoyin Kayode, Ajoke (2024)
Cooperative societies provide channels for sharing of input where women farmers can pool their limited resources together to maximize agricultural output and food security in rural areas. This study, therefore, analyzed factors influencing women farmers participation in agricultural cooperatives in Ondo State, Nigeria. The specific objectives of the research were to describe socio-economic characteristics of women farmer’s participation in agricultural cooperative societies, determine the level of participation of women farmers in agricultural cooperatives and examine factors that motivate participation. Data were analyzed using descriptive statistics, Likert type scale, and Pearson Product Moment Correlation analysis. The results revealed that women farmers in the study area were average aged (42.9 years) and mostly possessed tertiary education (38.3%), mean annual income (₦777,846) with farm size (0.8 hectares). The level of participation in agricultural cooperative is high (60.4%). Accessibility to loan (M. S= 3.50), getting information (M. S= 3.42) and input facility (M. S= 3.40) were top most factors that influenced participation in cooperatives among the women. At P< 0.05, Age, marital status and income realized per annum were positively significant to the level of participation in cooperatives. The study recommends the timely provision of loan to enable women farmers expand the scope of their farming activities, increased access to training programs for women farmer leaders in cooperatives as well as extension education should also be intensified.